An Analysis on Effect of Gender Towards Computer Literacy & E-Commerce - Pathmananathan, P. Ravindran; Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2021)
For its own development and governance, the Internet created a ground-breaking open model that involved all stakeholders. In an enormously connected world, Generation Y has been identified as the main consumer group that will bring change to the internet platform.. The aim of this study is to analyze the attitude and the Internet usage among the generation. This study was conducted using a questionnaire that was completed by 432 working professionals in the Kuala Lumpur Federal Territory and Selangor State, specifically MSC (Multimedia Super Corridor). It can be concluded that determinants such as gender and computer literacy influences internet moderators. in addition, as a moderator, the association between gender and computer literacy is imperative.